The role of the economic crisis on occupational stress and well being - Perrewe, Pamela L.; Halbesleben, Jonathon R. B.; Rosen, Christopher C. (Research in occupational stress and well being ;, 2012)
The recent economic recession has changed the nature of employment. Workers experience an increasingly uncertain future and many have been forced to search for jobs in a highly competitive market. In this volume, we call upon the fields leading researchers to examine how economic conditions relate to occupational stress and well being.